Proximal enterectomy provides a stronger systemic stimulus to intestinal adaptation than distal enterectomy. (1987) - Appleton, G V; Bristol, J B; Williamson, R C
Abstract : Enteroglucagon has been implicated as a tropic hormone in the control of intestinal adaptation. Because cells producing enteroglucagon are located mainly in the distal small bowel (and colon), ileal resection might be expected to produce less adaptive change than a jejunal resection of equivalent length. This hypothesis was tested in male Sprague-Dawley rats (n = 40) weighing 184.0 +/- 7.3 g and receiving a Thiry-Vella fistula (TVF) of the mid-60% of the small intestine. One group had concomitant resection of the jejunum proximal to the TVF (n = 12), another had resection of the ileum distal to the TVF (n = 13), while controls had a TVF alone (n = 15). When killed 10 days postoperatively rats with ileal resection weighed only 81% of controls (p less than 0.001) and 85% of those with jejunal resection (p less than 0.01). Jejunal resection produced an 81% increase in crypt cell production rate (measured by a stathmokinetic technique) over control values (28.5 +/- 4.2 v 15.8 +/- 2.3 cells/crypt/h: p = 0.025), whereas ileal resection had no demonstrable effect (17.5 +/- 2.3 cells/crypt/h). Adaptive hyperplasia in isolated small bowel is modulated by factors localised to the distal small intestine, enteroglucagon being a plausible candidate.